(untitled) (Brazilian Journal of Radiation Sciences (BJRS), 2022)
Approaches to form new materials for radiation dosimetry are essential to enhance quality assurance and quality improvement practices based on radiation protection concept. The present work reports a hydrothermal synthesis based on a relative low temperature and pressure to form thulium-yttria nanoparticles with electron paramagnetic resonance response. Thulium-yttria nanoparticles were prepared and characterized by XRD, SEM, PCS, and EPR. According to results, the hydrothermal method provided thulium-yttria nanoparticles with cubic C-type structure, mean particle size (d50) less than 160nm, and EPR response. The EPR spectra of powders exhibited two resonance peaks p1 and p2 recorded at 350 and 160mT, respectively. The enhancement of the EPR response of yttria by the use of thulium as a dopant provide meaningful parameters to advance in the formation of new rare earth based materials for radiation dosimetry.